Mesh Denoising of Developable Surfaces with Curved Foldings - Pan, Jiale; Bo, Pengbo; Li, Yifeng; Wang, Zhongquan (Computer aided design, 2024)
This paper presents a novel mesh denoising approach designed specifically for developable models with curved folds, going beyond traditional denoising metrics to focus on restoring the model’s developability. We introduce a metric based on normal variation to assess mesh developability and integrate it into an optimization problem that aims to increase the sparsity of the normal vector field, leading to a dedicated mesh denoising algorithm. The performance of our method is evaluated across a wide range of criteria, including standard metrics and surface developability determined through Gaussian curvature. Through testing on a variety of noisy models and comparison with several state-of-the-art mesh denoising and developability optimization techniques, our approach demonstrates superior performance in both traditional metrics and the enhancement of mesh developability. •We propose a metric using normal vector variation for surface developability.•We present a method to denoise a mesh while preserving developability and folds.•Our method surpasses existing ones in traditional metrics and developability.